AERIAL APPLICATION IN CLIMATIC CONDITIONS UNFAVOURABLE FOR THE CONTROL OF SOYBEAN RUST - Antuniassi, U. R. [UNESP] (2010)
UNESP, FCA, Dept Engn Rural, R Jose Barbosa de Barros 1780, BR-18610307 Botucatu, SP, Brazil